Auditing from a Distance: The Impact of Remote Auditing and Supervisor Monitoring on Analytical Procedures Judgments - Bhattacharjee, Sudip; Hillison, Sean M.; Malone, Carissa L. (The Accounting Review, 2024)
ABSTRACT As remote auditing remains widespread, the profession is concerned that decreased auditor-client interactions and remote supervision challenges can reduce audit quality. In response, some firms have increased supervisor monitoring of remote auditors. We experimentally examine how two key remote audit factors, the spatial distance between auditors and clients and the frequency of supervisor monitoring, influence auditors’ judgments in creative tasks. We predict and find that working remotely facilitates auditors’ higher-level cognition that enhances creative hypothesis generation and improves decision quality when uncovering a seeded error if monitored less frequently than more frequently. More frequent monitoring constrains auditors, which squashes effort and creativity, diminishing the benefits of working remotely. Working onsite at the client location reduces the sense of psychological distance, thereby diminishing the difference between monitoring frequencies. These findings have implications for audit practice as working remotely can enhance performance on creative problem-solving tasks, but only when monitored less frequently.